Entre a ética e a estética : a desmitificação do herói e da guerra em Soldados de Salamina e El impostor, de Javier Cerca - Lorena Carvalho dos Reis (2017)
Over the 20th and 21st centuries the Spanish Civil War became the greatest Spanish western. However, the tension between reality and fiction is one of the most important ideas in contemporary Spanish literature. Shedding light on themes such as wars and their historical characters, fiction tends to touch wounds of sensitive themes, evoking in their fictional fabrics extra-literary discussions. In the novels Soldiers of Salamis (2001) and The Impostor (2014), both of the Spanish writer Javier Cercas, we find a body that typifies this issue due to its controversial treatment given to recent memory and history. Likewise, in view of the myth built around Rafael Sánchez Mazas, co-founder of the Spanish Falange, and his miraculous escape from a mass shoot-out in 1939, as well as the unmasking of the Catalan Enric Marco, a false survivor of the Shoa, this dissertation aims at testing the narrative strategies of demystification of the war and the hero carried out in these two texts. Thus, taking a tour of the main theories around these themes, we will present and discuss the roles of propaganda and nationalist mythology in the forging of heroic images such as that of Sánchez Mazas and, from the Marco case, we will also analyze the processes of memory cleavage exercised by the historians of the house with their impact on the memory of the survivors of Nazism.